Isolation and Characterization of Entomopathogenic Fungi from the Soil of Badakhshan Province and Their Mycoinsecticidal Effects Against Subterranean Termite (Anacanthotermes vagans) - Fallahzadah, Muhammad Hussain; Rahimi, Muhammad Salim (Journal of Natural Sciences – Kabul University, 2020)
A survey of entomopathogenic fungi (EPF) in Badakhshan province identified two species: Metarhizium robertsii and Metarhizium anisopliae, using both morphological and molecular methods. For mass production of EPF, two isolates, including B. bassiana and M. robertsii, were cultivated with four different raw substrates (broken rice, broken wheat, green gram, and sawdust) using solid-state fermentation. The M. robertsii strain produced the highest total conidial yields after 18 days on broken rice, while the highest conidial yields for B. bassiana were obtained after 18 days on green gram. The conidial suspension was applied against subterranean termites, Anacanthotermes vagans, at four different concentrations (1×10^5, 1×10^6, 1×10^7, 1×10^8 conidia/mL). The highest mortality rate was observed at 1×10^8 conidia/mL for both M. robertsii and B. bassiana. In general, the indigenous isolate M. robertsii was more virulent than B. bassiana, while B. varroa did not affect termites.